Microstructural Characterization of Improved Formability of Ti-6Al-4V Sheet by Pulsating Hydraulic Bulging at Room Temperature - Yapan, Yusuf Furkan; Ozturk, Osman; Turkoz, Mevlut; Dilmec, Murat; Livatyali, Haydar; Halkaci, Huseyin Selcuk; Kotan, Hasan (SPRINGER, 2023)
This study aims to increase the limited formability of the Ti-6Al-4V sheet at room temperature using the pulsating hydraulic bulging and to investigate the microstructural reasons for the increased formability. Accordingly, monotonic and pulsating hydraulic bulge tests (HBTs) were applied to Ti-6Al-4V sheets with 0.55 mm thickness at room temperature, and the underlying microstructural reasons for the improved formability were investigated by conducting detailed microstructural characterizations. The experimental results showed that the pulsating HBT samples reached 15.4% higher bulge dome height than the monotonic HBT samples, and a more homogeneous thickness distribution was achieved by pulsating bulging. The thickness and microhardness distributions, dislocation density estimations, and fracture surface analysis were utilized to correlate the increased formability with the microstructure. It was determined that stress relaxation occurred during the pulsating HBT, resulting in the achieved improved formability. The decrease in the dislocation density in the early stage of forming prevented the locking of the dislocations and delayed the occurrence of the damage, i.e., leading to the increased bulge dome height. The higher plastic deformation resulting from the increased formability also increased the hardness along the cross-section. The increased formability of the Ti-6Al-4V sheet during the pulsating HBT and the underlying microstructural phenomena elaborated in this study are expected to make significant contributions to the current literature on the sheet metals with limited formability at room temperature.
Keywords: formability; microstructural characterization; pulsating hydroforming; stress relaxation; sheet metal forming; Ti-6Al-4V; STRESS-RELAXATION; MECHANICAL-PROPERTIES; TI-6A1-4V ALLOY; TITANIUM; BEHAVIOR; STRAIN; 304-STAINLESS-STEEL; OPTIMIZATION; DUCTILITY; Materials Science